The Impact of Mortality Salience on Intergenerational Altruism and the Perceived Importance of Sustainable Development Goals - Hu, Saiquan; Zheng, Xiaoying; Zhang, Nan; Zhu, Junming (Frontiers in Psychology, 2018)
The Sustainable Development Goals (SDGs), consisting of 17 specific goals such as ending poverty, reducing inequality, and combating climate change, were proposed by the UN member states in 2014 for the ongoing UN agenda until 2030. These goals articulate the growing need for the international community to build a sustainable future. To progress and build a truly sustainable future requires not only the immediate support of individuals for the current SDGs, but also their personal long-term commitment to the needs of future generations (i.e., intergenerational altruism). Reminders of death can influence attitudes, motivation, and behavior in various aspects of our lives. In the current research, we thus explored whether reminding individuals of their own death will influence their intergenerational altruism and perceived importance of the SDGs. Using a three-condition (mortality salience vs. dentist visit vs. neutral) randomized experiment, we found that mortality salience led participants to place a higher priority on the needs of future generations only when compared to the neutral condition. Further, we conducted a factor analysis that generated two SDGs factors (socially related SDGs and ecologically related SDGs). We found that mortality salience reduced participants’ perceived importance of the socially related SDGs when compared to both the dentist visit and the neutral conditions, and mortality salience decreased participants’ perceived importance of the ecologically related SDGs only when compared to the neutral condition.